Causal association among smoking, bitter beverage consumption, and risk of osteoporosis: a two-sample mendelian randomization-based study - Yanqian Wu; Jianqian Chao; Min Bao; Na Zhang; Leixia Wang (Hereditas)
Abstract Objectives Two-sample MR methods were employed to analyze the impact of smoking and bitter beverage consumption on the risk of osteoporosis and osteoporosis with pathological fractures, in order to assess the causal association. Methods Publicly available genome-wide association study summary data were analyzed using MR methods. The exposures investigated were smoking (smoking per day, smoking initiation, and lifetime smoking index) and bitter beverages (coffee, tea, bitter alcoholic beverages, bitter non-alcoholic beverages, and total bitter beverages). The outcomes examined were the risk of osteoporosis and osteoporosis with pathological fractures. The inverse-variance weighted (IVW) method was used as the main statistical model. The stability and reliability of the results were verified by the Cochran’s Q test, the Egger-intercept test, and the leave-one-out analysis. Results Smoking per day was causally associated with the risk of osteoporosis OR = 1.417, 95% CI = 1.119–1.794, P = 0.003), and lifetime smoking index had a possible genetic causal association with the risk of osteoporosis with pathological fractures (OR = 4.187, 95% CI = 1.909–9.184, P < 0.001). No genetic causal association was found between smoking initiation or lifetime smoking index and the risk of osteoporosis (P > 0.05). No genetic causal association was identified between smoking per day or smoking initiation and the risk of osteoporosis with pathological fractures (P > 0.05). Total and bitter non-alcoholic beverage consumption showed a potential effect on the risk of osteoporosis (OR = 3.687, 95% CI = 1.535–8.858, P = 0.003 and OR = 3.040, 95% CI = 1.466–6.304, P = 0.002, respectively). Conclusions This study found smoking raises the risk of osteoporosis and osteoporosis with pathological fractures based on genetics. Certain bitter beverages are linked to an increased osteoporosis risk.